ChemInform Abstract: Iminoxyl Radical‐Based Strategy for Intermolecular C—O Bond Formation: Cross‐Dehydrogenative Coupling of 1, 3‐Dicarbonyl Compounds with Oximes. Issue 51 (23rd December 2014) - Krylov, Igor B.; Terent'ev, Alexander O.; Timofeev, Vladimir P.; Shelimov, Boris N.; Novikov, Roman A.; Merkulova, Valentina M.; Nikishin, Gennady I.
Abstract Numerous other diketones, 1, 3‐keto esters and oximes are investigated.